Pengaruh Budaya Organisasi, Motivasi Kerja, dan Kepuasan Kerja terhadap Kinerja Dosen Manajemen (Studi Empiris di Perguruan Tinggi Keresidenan Bojonegoro) - Anas Ahmadi, Edy; Herwidyaningtyas, Fristina Bhakti; Fatimah, Siti (Journal of Industrial Engineering & Management Research, 2020)
This study aims to analyze and describe the direct and indirect influence between organizational culture, work motivation on the performance of lecturers through accounting faculty job satisfaction throughout bojonegoro residence. The population in this study is the whole Lecturer in Accounting at the University Bojonegoro residence. While the sampling technique used is proportionate stratified random sampling. The analysis used in this study is Part Analysis Method, which previously conducted validity and reliability. Based on calculations indicate that variable of organizational culture on job satisfaction is significant. Based on the calculation results show that the variables of work motivation on job satisfaction is significant. Job satisfaction as be intervening variables between organizational culture with the performance of lecturer. Job satisfaction as be an intervening variable between motivation to work on the performance of the lecturer. Based on the test results showed that the variables of job satisfaction on the performance of the lecturer is significant. Adjusted R square of 0.543 indicates that 54.3 percent of the variance explained by the performance of the lecturer is the independent variable and intervening variables in the regression equation. While 45.7 percent is explained by other variables not examined in this study.